First Report of Candida tropicalis in Edible Freshwater Fish in the Philippines - Milanez, Giovanni De Jesus; Lirio, Mary Rose Ferrer; Hagosojos, Bernardino Manikis; Masangkay, Frederick Ramirez (Asian Journal of Biological and Life Sciences, 2019)
In the course of establishing Free-Living-Amoeba (FLA) biodiversity from the intestines of edible freshwater fishes all over the Philippines, the presence of cyst-like structures in amoeba culture plates were observed, subjected to molecular identification and was later confirmed to beCandida tropicaliswhich is an emerging pathogenic yeast cell. This is the first report of a pathogenic yeast cell in an edible freshwater fish in the Philippines and is an important consideration as a possible source of fungal infection for humans, in particular individuals with immunocompromised status.
Keywords: Candida; Fish; Freshwater; Lakes; Philippines; Yeast